Vanilla distribution modeling for conservation and sustainable cultivation in a joint land sparing/sharing concept - Watteyn, Charlotte (2020)
Se seleccionó la licencia Creative Commons para este envío. El documento trae lo siguiente: © 2020 The Authors. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited. E-mail: bart.muys@kuleuven.be